Studying Surface Water Quality in the Upstream of Ba River Basin in Gia Lai Province - Thi Thu Ha, Pham; Thi Lien, Tong; Ngoc Anh, Ngo; Ngoc Bach, Duong; Hong Hanh, Hoang; Thi Van Anh, Nguyen (VNU Journal of Science: Earth and Environmental Sciences, 2024)
This study used two data sets to evaluate the surface water quality in the upstream of Ba River basin in Gia Lai Province in 2022. The first collected data set included six monitoring periods in April, May, July, September, November, and December in 2022 with 22 surface water samples each time at 22 points in Gia Lai. The second data set was monitored additionally, focused on the monitoring points in the Ba River basin in Gia Lai, including 38 monitoring points: 28 points on the Ba River and 10 points on 4 major river tributaries in the Ba River basin, with 10 samples for each point during the period from April 4 th , 2022 to May 2 nd , 2022. Results from processing the first data set showed that there were 4/22 points having water quality at the level from poor to very heavily polluted needing special attention, including: 3 points measured in the dry season (N1 - Tra Da Industrial Park, Pleiku City, N17 - receiving wastewater from Chu Se Industrial Park, and N23 - Phu Tuc town, Krong Pa) and 1 point measured in the rainy season in July (N11 -Yang Trung Bridge, Kong Chro district) where the water quality was heavily polluted with WQI = 8. Results from processing the second data set showed that the water quality of the Ba River tended to gradually degrade along the flow. There are 3 monitoring points in the upstream of Ba River with the water quality reaching level C (bad water quality): NN_Song Ba_1, NN_Song Ba_2, and NN_Song Ba_3. The remaining points reached level D (very poor water quality). These locations with poor water qualities need appropriate measures to improve water quality. This research results will be the basis for developing a surface water quality management plan in Gia Lai province and Ba River basin.